1992
DOI: 10.1002/tox.2530070207
|View full text |Cite
|
Sign up to set email alerts
|

A bloom of Prymnesium parvum Carter in a small coastal inlet in Dragsfjärd, southwestern Finland

Abstract: A bloom of Prymnesium parvum Carter and fish mortality occurred in June 1990 in a coastal inlet in Dragsfjärd, southwestern Finland. The highest concentrations of P. parvum exceeded 50,000 cells/mL. Chemical analyses done in early July during the decline of the bloom showed total phosphorus values of 30–36, total nitrogen values of 710–810, and chlorophyll a concentrations below 10μg/L. The levels were about 50% lower in the archipelago outside the inlet where low numbers of P. parvum occurred. Flagella of liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

1992
1992
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…Highest upregulation was observed in stationary phase nutrient-replete cultures, where the pH of the medium reached up to 9. Such a high pH is a common phenomenon in natural blooms where during dense P. parvum blooms the pH can even exceed 9 (Lindholm and Virtanen, 1992;Michaloudi et al, 2009). As photosynthetic cells grow and increase in concentration the pH of the medium increases in a closed system (e.g.…”
Section: Genes Expressed In the Different Growth Phasesmentioning
confidence: 99%
“…Highest upregulation was observed in stationary phase nutrient-replete cultures, where the pH of the medium reached up to 9. Such a high pH is a common phenomenon in natural blooms where during dense P. parvum blooms the pH can even exceed 9 (Lindholm and Virtanen, 1992;Michaloudi et al, 2009). As photosynthetic cells grow and increase in concentration the pH of the medium increases in a closed system (e.g.…”
Section: Genes Expressed In the Different Growth Phasesmentioning
confidence: 99%
“…For example, in Norway P. parvum was found to destroy fish gills, thus causing mass mortality of farmed fish (Aure & Rey 1992). In the Baltic Sea, P. parvum belongs to the natural plankton community and may, in suitable environmental conditions, bloom with harmful effects (Lindholm & Virtanen 1992, Lindholm et al 1999). …”
Section: Introductionmentioning
confidence: 99%
“…Neither of the cultures was axenic, and both algae were isolated from the Baltic Sea, where Thalassiosira spp. usually precede P. parvum in annual succession (Edler 1979, Lindholm & Virtanen 1992. Besides using species from the same environment, we chose these 2 species because it has been demonstrated that the algal allelopathic effect is usually more significant on groups preceding the allelopathic algae, since allelopathy can be used to achieve dominance over the predecessor group (Keating 1977.…”
Section: Introductionmentioning
confidence: 99%